Análise de gestão de custos em uma empresa de britagem - Mezzomo, Mateus Agador (2021)
This work presents an analysis of cost management in a crushing company, in view of the increase in competition, thus providing a competition for prices and sales, where whoever can reduce costs will obtain a greater profit. With the objective of elaborating a proposal for the management of costs in a crushing company, the current situation of the production system and its costs was analyzed, the expenses related to the production of crushed stone were identified and a proposal was prepared to reduce costs. Through the case study, it was found that the establishment has a variation in profit in the analyzed period, and it was noted that there is a large expenditure on electricity. For this reason, a proposal for the implementation of the photovoltaic energy system was prepared, even though the investment is large, but in return it will be saving about 90% of energy in the same period. Proving through calculations and graphics to be viable, the proposal obtained a satisfactory result, where the company will have a great economy in the next 25 years.